FENOMENA JUDI POKER ONLINE DIKALANGAN MAHASISWA UNIVERSITAS RIAU JURUSAN SOSIOLOGI - Agus Ari Apriansyah; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was carried out among University Students of Riau. Phenomenon gambling poker on line among college student university of Riau Majors sociology. (1).how mechanism online gambling poker among students university of riau majors sociology(2). what is the impact online gambling poker among students university of riau majors sociology. This research is qualitative descriptive research. As for the sample in this study is University of Riau students who do and know gambling online poker. Because the number of students who do online gambling poker is unknown, hen in this study the authors in the sampling technique used on probability is Snowball Sampling technique by determining one or two informants to be interviewed further from the previous informants get informed next information. To collect research data using observation method, documentation, and in-depth interview using interview guideline in analyzing data of research result used qualitative analysis and in its writing described in descriptive. Based on the results of research can be concluded that the behavior of online gambling poker among students is caused by factors that are factors of longgars control of parents, profit factors, factors desire and friend factors that affect. And the impact of this online behavior is the health impact, lowered the spirit of learning,economy, personality and result in such deviant behavior that is lying, pawning goods as well as the positive impact of poker online gambling is that as entertainment.Keywords: Gambling, poker online, pekanbaru